"If f(x) = 4x, g(x) = 2x – 1 and h(x) = x2 + 1, find each value."
a. h[g(4)]
b. f[f(-3)]
c. g[h(-1/2)]
d. [f ○ (h ○ g)](3)
I don't really know where to start with this question so any help on it would really be appreciated.
a) first calculate g(4) (replacing x by 4 in the expression of g(x)), and then calculate the $\displaystyle h$ of that value.
idem for b) c)
d) $\displaystyle f\circ g(x) = f[g(x)]$, so what is $\displaystyle [f\circ (h\circ g)](x)$ ? and use the same reasoning as in a)
not factoring ... this is function composition.
a. h[g(4)]
first calculate g(4) ...
g(x) = 2x - 1
g(4) = 2(4) - 1 = 7
h[g(4)] = h(7) = (7)^2 + 1 = 50
you do b and c.
d. [f ○ (h ○ g)](3) = f[h[g(3)]]
start by evaluating g(3) , then h[g(3)], then f[h[g(3)]] ... work inside out.